OBTENÇÃO E ESTUDO DAS PROPRIEDADES FÍSICO-QUÍMICAS DE AMIDOS DE MANDIOCA (Manihot esculenta) OXIDADOS E ÁCIDO-MODIFICADOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
Cassava starch presents technological properties that make it highly valued for certain applications. It has a unique bland flavor as well as its viscographic pattern during cooking. In this work, cassava starch was modified by treatment with sodium hypochlorite (NaClO) (0.8, 2 and 5% of active chlorine/ 100 g of starch) and acid hydrolysis with hydrochloric, sulfuric, phosphoric (0.06; 0.15 and 1 mol L-1) and lactic (10 and 50 %) acids. The physicochemical properties of oxidized and partially hydrolyzed starches were studied. The native and modified samples were evaluated considering moisture, differential dyeing, carboxyl content, reducing power and extrose equivalent (DE), apparent viscosity analysis, susceptibility to syneresis and clarity of the pastes. The native and modified starch samples were evaluated by infrared spectroscopy (FTIR) with chemometric analysis. The carboxyl content, reducing power and DE of the oxidized starches (2 e 5 %) increased with increasing NaClO concentration. Reducing power of the acid-modified starches increased after modification, H3PO4 causing the least and HCl the highest value. The transmittance (T %) values of the native and modified starch pastes were measured out at 650 nm. Oxidized and modified inorganic acids starch pastes showed a considerably higher T % than the native starch. The average values obtained with more concentrated reagents were: 99.7 %T for the oxidized, 74.1, 64.4 and 64.2 %T for the HCl, H2SO4 and H3PO4, respectively, and 17.0 %T for the lactic acid. In the differential dyeing, the oxidized starches presented a higher blue color when compared to the native starch. This different adsorption of methylene blue should be due to the presence of carboxyl groups formed by oxidation. In the syneresis, all modified starches by inorganic acid showed higher water liberation than the oxidized starches. Modified starches with lactic acid were more stable, with the values of syneresis little higher than the native starch. Apparent viscosity analysis showed decrease in the peak viscosity of oxidized and acid-modified starches. Alterations of the physicochemical properties could be attributed to partial cleavage of the glycosidic linkages resulting from introduction of carboxyl groups (COOH) after oxidation. Acid hydrolysis partially degraded the starch molecules; with inorganic acids most severe degradation was obtained with HCl and least with H3PO4. The acid-modified starch with lactic acid showed distinct characteristics from that of the acid-modified starches with inorganic acids such as greater integrity of the molecular chain of starch. The principal component analysis (PCA) of the infrared spectra allowed separation between native and modified samples probably due to changes in relative crystallinity and carboxyl group contents formed by oxidation of cassava starch.
Keywords: amido; mandioca; oxidação; hidrólise; propriedades físico-químicas; viscosidade; FTIR; starch; cassava; oxidation; hydrolysis; physicochemical properties; viscosity; FTIR; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS